Abstract ID: 223 The promise of the MRI linac: Simultaneous MRI and irradiation. (October 2017) - Raaymakers, Bas; Lagendijk, Jan
Abstract : Introduction: Image guidance during radiotherapy is widely applied in the current clinic. Prior to treatment a variety of imaging modalities is used to localize and characterize the tumour and the surrounding organs at risk. These data are used to optimize the treatment plan, i.e. optimize the radiation dose delivery. Still, during the course of radiotherapy many sources of geometrical uncertainties exist, leading to treatment margins and with that to unwanted involvement of healthy tissues in the targetted volume. By integrating 1.5 T MRI functionality with a radiotherapy linear accelerator (linac), the anatomy can be visualized during irradiation and thus decreasing the geometrical uncertainties and improve the targetting. Materials and methods: Together with Elekta (Stockholm, Sweden) and Philips (Best, The Netherlands) a 1.5 T MRI system is integrated with a 7.2 MV linac. The active shielding of the MRI as well as the layout of the linac is modified to mitigate the magnetic interference. A dedicated cage of Faraday was designed to mitigate the RF interference and a beam window in the MRI was created to allow beam passage. In parallel with the hardware developments a pipeline for daily online and ultimately real-time plan adaptation has been set-up. This enables to adapt the plan as soon as an anatomical change is detected. The pipeline can re-optimize the treatment plan for the latest state of the anatomy while taken into account the dose delivered so far. This loop can be run daily but also on an intra-fraction time scale. A major deviation from conventional systems is that the dose is delivered in the presence of a magnetic field. This affects the dose distribution but also affects dosimeters. The impact of the magnetic field can be investigated and subsequently accounted for by Monte Carlo simulations. By doing so, we can quantify the impact on dose and dosimeters. Results and discussion: The first prototype MRI linac gave the proof of concept for simultaneous irradiation and MRI. The second prototype showed MRI guided IMRT. The third prototype in Utrecht is the pre-production MR linac and currently the fourth MR linac is installed, this is the pre-clinical MR linac that will be introduced in the clinic. Currently the system is being accepted and commissioned for clinical introduction. The adaptive treatment pipeline has been shown to converge for regular clinical plans. Also for changing anatomies over the course of days and for changes during a single fraction the dose distribution converges to a clinically acceptable dose distribution. Currently the loop is fast enough, in the order minutes, for daily plan adaptation. We are working on speed optimization for the intra-fraction applications. The impact of the magnetic field has been shown to be an asymmetry in the penumbra, a reduced built updistance and most strikingly a dose increaseat tissue-air interfaces. It was shown that these effects can be mitigated by incorporating the magnetic field effects in the inverse optimization for IMRT. Also the impact on absolute, reference and relative dosimetry has been addressed. All exisiting dosimetry protocols can still be performed, albeit sometimes with adapted procedures and adapted detectors. In summary, the 1.5 T MRI linac is operational in a research setting and work on the clinical introduction is ongoing. The advent of on-line MRI directly from the treatment table enables true on-line adaptive radiotherapy.